تشكل الفضاء والزمن الأسطوري في رواية عشب الليل لإبراهيم الكوني - مدوري, نوال (Revues faculté des lettres et des langues, 2018)
Abstract: ' The grass of the night' , a novel written by Abderrehmene Elkououni, where a deep interaction is experienced The latter different epistemic and ideological sources, which had contributed to the birth of a rich text in matter of allusions, especially the mythic source which gave the text on artistic and aesthetic dimension by shaping the novel’s structure in order to establish an ironic context underlying the logic of myth. In this respect, we came to select in this study two textual aspects: space and time, to explore how they contributed to mythic structureingredient ? الملخص لقد تفاعل النص الروائي "عشب الليل" لإبراهيم الكوني مع روافد معرفية وفكرية مختلفة، أسهمت في ميلاد نص مكتنز بطاقات إيحائية ثرّة، منها الرافد الأسطوري الذي أكسب النص بعدا فنيا وجماليا خاصة عندما تسرب إلى مقوماته البنائية بهدف خلق أجواء مفارقة وفق منطق الأسطورة والتي اخترنا من بينها ( الفضاء والزمن )حيث منحتهما الأسطورة نزوها مفارقيا فكيف تشكلت مفردات ذلك داخل المكون الأسطوري؟